2021
DOI: 10.1080/21691401.2021.1984935
|View full text |Cite
|
Sign up to set email alerts
|

Copper oxide (CuO) and manganese oxide (MnO) nanoparticles induced biomass accumulation, antioxidants biosynthesis and abiotic elicitation of bioactive compounds in callus cultures of Ocimum basilicum (Thai basil)

Abstract: Copper oxide (CuO) and manganese oxide (MnO) nanoparticles induced biomass accumulation, antioxidants biosynthesis and abiotic elicitation of bioactive compounds in callus cultures of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Cultivated plants with Cd- and Pb-contaminated soils showed a major influence on the EOs’ yield, composition, and phytoremediation of the soil ( Youssef, 2021 ). In addition, RA, chicoric acid, and eugenol were higher when cultured in CuO-NP media ( Nazir et al, 2021 ). Increase salicylic acid and its β-glucoside cause to accumulation of jasmonic and abscisic acids in O. basilicum due to foliar-spraying treatment with U. intestinalis extract and the essential oil (EO) chemotype changed from methyl eugenol/eugenol to epi-α-cadinol and increased sesquiterpenes ( Paulert et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cultivated plants with Cd- and Pb-contaminated soils showed a major influence on the EOs’ yield, composition, and phytoremediation of the soil ( Youssef, 2021 ). In addition, RA, chicoric acid, and eugenol were higher when cultured in CuO-NP media ( Nazir et al, 2021 ). Increase salicylic acid and its β-glucoside cause to accumulation of jasmonic and abscisic acids in O. basilicum due to foliar-spraying treatment with U. intestinalis extract and the essential oil (EO) chemotype changed from methyl eugenol/eugenol to epi-α-cadinol and increased sesquiterpenes ( Paulert et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, our findings are in accordance with the recent result reports. For example, a supplement of NPs to the plant media has increased phenolic compound production ( Jadczak et al, 2020 ; Nazir et al, 2021 ). The increase in phenols and flavonoids production may be due to ROS generation by NPs that starts complicated reactions and affects metabolic processes in the plant cells ( Hatami et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, induction factors are needed to enhance the productivity of phytochemical compounds from medicinal plants for nutritional and pharmaceutical purposes. Using NPs for bioactive component induction is one of the prioritized strategies for the sustainability of bioactive component production ( Tian et al, 2018 ; Vargas-Hernandez et al, 2020 ; Nazir et al, 2021 ). Therefore, the impact of biogenic AgNPs on bioactive compounds like coumarin, tannic acid, quercetin, rutin, gallic acid, and hesperidin production from callus was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They explored several plant growth regulators and found that 5 mg/L 6-benzylaminopurine (BAP) combined with 1 mg/L naphthalene acetic acid (NAA) yielded the best phenolic yield (346.08 mg/L), including 7.4 mg/g RA [ 28 ]. Subsequently, callus of basil grown on a medium supplemented with 10 mg/L CuO-NPs yielded the highest RA accumulation (11.4 mg/g) [ 29 ]. Light-emitting diode irradiation increased the RA content of callus 96.0 mg/g, 2.46-fold higher than control [ 30 ].…”
Section: Culture Techniques Extraction Processes and Anti-tumor Appli...mentioning
confidence: 99%